Material analysis of spontaneously subluxated Iris-fixated phakic intraocular lenses - Tandogan, Tamer; Holzer, Mike P.; Choi, Chul Y.; Auffarth, Gerd U.; Khoramnia, Ramin (Journal of refractive surgery, 2016)
Journal of Refractive Surgery | This article has been amended to include factual corrections. To read the erratum, click here. The online article and its erratum are considered the version of record. - PURPOSE: - To conduct a material analysis of spontaneously subluxated iris-fixated phakic intraocular lenses (IOLs) using light and scanning electron microscopy. - - METHODS: - Six explanted Artisan/Verisyse and Artiflex/Veriflex IOLs
Gesehen am 02.06.2020